ANALISIS KELAYAKAN DAN MANAJEMEN RISIKO INVESTASI DALAM PEMBUATAN “QUARY ANDESIT” UNTUK MEMENUHI KEBUTUHAN PROYEK TOLL BOCIMI “BOGOR CIAWI SUKABUMI” - Wahid Agung; Fitri Nugraheni; Rossy Armyn M; Albani Musyafa (JOURNAL SAINS STUDENT RESEARCH, 2024)
The Bocimi Toll construction project in the Bogor - Sukabumi area is one of the national strategic projects initiated by the government, according to (Indonesiabaik.id, 2017) this project costs an investment of Rp. 7.77 trillion. With these conditions, the need for aggregate material should be large and this quarry business is attractive to run, but in the process the quarry built by PT. TS experienced operational closures, therefore the author wants to evaluate and conduct an analysis related to the investment made.This analyzes using the formula (Net Present Value), (Internal Rate Of Return) and (Payback Period) and identifies the risks that will occur in a quarry construction so that it can be a decision maker when a construction project or someone will open a quarry. In the research conducted, the total investment value was obtained of Rp. 2,300,000,000 and this business process is planned to run for 5 years, the NPV value was obtained with an Interest value of 10.94% positive Rp.34,848,413,722, the IRR value of 51% is greater than the MARR value determined at 15% and the Payback Period value of 0.7 years this business is considered feasible, then conducting a literacy study and interviews obtained 26 variables, there are 9 variables classified as medium risk and 17 high risk variables, Risk response based on probability and impact values ​​there are owners who have 4 variables with the status of risk avoidance, 3 transfer variables and 1 risk reduction variable. The implementer has 3 risk avoidance variables, 6 risk transfer variables and 1 risk reduction variable. The community has 3 risk avoidance variables.Consumers/project owners have 3 risk avoidance, 1 risk transfer and 1 risk reduction. After the variables from the risk analysis are known, they are re-sorted where the risk factors that can increase the cost burden in investment are then analyzed and the costs incurred are known to be Rp. 1,004,222,260 of that value adds to the capital value, then the NPV value is obtained of Rp. 30,127,078,830 has a positive value, the IRR value is known to be 49% is said to be feasible because it exceeds the MARR value, and after calculating the Payback Period value, it is obtained 1.1 years, analytically it can be said that it is still feasible to run. In this study, risk factors that cannot be assessed are also expected to be a reference for ongoing investment considerations, this is to avoid a loss in the construction of the quarry.